Effects of group cognitive behavior therapy on cognitive flexibility in college students with high obsessive-compulsive symptoms - Ji, Sifan; Liu, Yingying; Chen, Lu; Zhang, Wei; He, Kongliang (Frontiers in Psychology, 2025)
ObjectiveTo explore the effect of group cognitive behavior therapy on cognitive flexibility in college students with high obsessive-compulsive symptoms.MethodsFifty-eight college students were randomly divided into an experimental group and control group (29 in each group). The experimental group was treated with group cognitive behavior therapy (twice a week for 4 weeks) whereas the control group was untreated. Before and after the intervention, the two groups of students were tested with the obsessive-compulsive scale OCI-R, cognitive flexibility scale CFI, acceptance and action questionnaire AAQ-II, and the cognitive fusion questionnaire CFQ to evaluate the effect after the intervention.ResultsIn the total score of obsessive-compulsive scale, the interaction between measurement time and groups was significant (F(1,56) = 17.563, p < 0.001). The post-test score of the experimental group was significantly lower than that of the pre-test score, and there was no significant difference in the control group before and after the intervention. In the total score of the cognitive flexibility scale, the interaction between measurement time and groups was significant (F(1,56) = 6.616, p < 0.05). The post-test score of the experimental group was significantly higher than the pre-test score, and there was no significant difference in the control group before and after the intervention. In the second edition of the action questionnaire and the cognitive fusion questionnaire, the interaction between measurement time and groups was significant (F(1,56) = 18.887, p < 0.001). The post-test score of the experimental group was significantly lower than that of the pre-test, and there was no significant difference in the control group before and after the intervention.ConclusionTaken together, our results show that group cognitive-behavioral therapy significantly improved the cognitive flexibility of college students with high obsessive-compulsive symptoms, resulting in a significant reduction of these symptoms.